Modelling the effects of modified local starches on the rheological and filtration properties of a water – based drilling fluid (2021)
This study is designed for the comparative analysis of chemically modified local starches used as additive in improving the rheological and fluid loss properties of a water- based drilling fluid. Additives are added to a drilling fluid in order to enhance the various functions of the drilling mud. Different drilling fluid samples were formulated without additive and with various concentrations modified starches. A laboratory investigation on the drilling fluid rheological and filtration properties using the API recommended standard procedures, pressure were studied at 1000 psi with a temperature range of 40.0 to 180.0 ° C, using a High Pressure High Temperature, (HTHP) rheometer and Fann Model 35A respectively From the analyses of the experimental results, it was observed that effective viscosity, plastic viscosity and yield point decrease steadily with increase in temperature. The experimental results, water based drilling fluid treated with chemically modified local starches improves the filtration and rheological properties of the drilling mud. Finally, this paper also presents a predictive model equation good enough to analyse trends and predict future values for effective and plastic viscositie